Rise of the authoritarian state in peripheral societies - Thomas, Clive Y. (Monthly Review Press New YorkUS, 1984)
Traces development of the state system from colonization to independence and examines the economic, political and social features of peripheral states. Argues that the authoritarian state has risen in the context of underdeveloped productive forces, no hegemonic bourgeoisie and where the working class is weak. Examines mechanisms by which the ruling class wins acceptance in the absence of democratic restraints. These range from nepotism and corruption to manipulation of the electoral process, terror and assassination. Discusses the importance of democracy for capitalists and socialists alike and the implications of this study for political struggle in the third world.